Acrylamide adsorption by Enterococcus durans and Enterococcus faecalis: In vitro optimization, simulated digestive system and binding mechanism - Albedwawi, Amal S.; Al Sakkaf, Reem; Osaili, Tareq M.; Yusuf, Ahmed; Al Nabulsi, Anas; Liu, Shao-Quan; Palmisano, Giovanni; Ayyash, Mutamed M. (Frontiers in Microbiology, 2022)
Acrylamide is an unsaturated amide that forms in heated, starchy food products. This study was conducted to 1) examine the ability of 38 LAB to remove acrylamide; 2) optimize acrylamide removal of selected LAB under various conditions (pH, temperature, time, and salt) using the Box-Behnken design (BBD); 3) the behavior of the selected LAB under the simulated gastrointestinal conditions; and 4) investigate the mechanism of adsorption. Out of the 38 LAB, Enterococcus durans and Enterococcus faecalis had the highest results in removing acrylamide, with 33% and 30% removal, respectively. Those two LAB were further examined for their binding abilities under optimized conditions of pH (4.5 - 6.5), temperature (32°C - 42°C), time (14 - 22 hours), and NaCl (0% - 3% w/v) using BBD. pH was the main factor that influenced acrylamide removal compared to other factors. E. durans and E. faecalis exhibited acrylamide removal of 44% and 53%, respectively, under the in vitro digestion. Zeta potential results indicated that the changes in the charges were not the main cause of acrylamide reduction. Transmission electron microscopes (TEM) results indicated that the cell walls of the bacteria increased when cultured in media supplemented with acrylamide.